SOIL WATER BALANCE, BIOMASS AND YIELD OF POTATO CROP (Solanum tuberosum L.) GROWN IN HIGH ALTITUDE HUMID TROPICS OF INDONESIA - R Salwati; I Handoko (SEAMEO BIOTROP, 2012)
This research calculated water loss through actual evapotranspiration and runoff (ETa+Ro) of potato crop in high altitude of humid tropics in Indonesia by using water balance approach. The treatments consist of two row spacings and three seed sizes for sowing. Soil water contents of six combination of treatments were measured weekly to the soil depth of 100 cm to calculate water loss by actual evapotranspiration and runoff. Water loss by ETa+Ro was much higher (average of 18.2 mm/day) compared to average potential evapotranspiration (7.5 mm/day). Despite high rainfall during the growing season (1314 mm), actual evapotranspiration could reduce soil water content to 60 cm soil depth due to the high runoff caused by limited capacity of water infiltration into the soil. Total ETa+Ro averaged for all treatments was 1365 mm which was comparable among treatments. Higher soil water content resulted in larger crop biomass and higher tuber yield. On the other hand, larger seed size produced greater crop biomass and tuber yield irrespective of the variation of soil water contents in the treatments.